British Columbia Vegetation and Climate History with Focus on 6 ka BP - Hebda, Richard (Géographie physique et Quaternaire, 1995)
ABSTRACTBritish Columbia Holocene vegetation and climate is reconstructed from pollen records. A coastal Pinus contorta paleobiome developed after glacier retreat under cool and probably dry climate. Cool moist forests involving Picea, Abies, Tsuga spp., and Pinus followed until the early Holocene. Pseudotsuga menziesii arrived and spread in the south 10 000-9000 BP, and Picea sitchensis - Tsuga heterophylla forests developed in the north. T. heterophylla increased 7500-7000 BP, and Cupressaceae expanded 5000-4000 BP. Bogs began to develop and expland. Modern vegetation arose 4000-2000 BP. There were early Holocene grass and Artemisia communities at mid-elevations and pine stands at high elevations in southern interior B.C. Forests expanded downslope and lakes formed 8500-7000 BP. Modern forests arose 4500-4000 BP while lower and upper tree lines declined. In northern B.C. non-arboreal communities preceded middle Holocene Picea forests. Abies, Pinus and Picea mariana predominated at various sites after 4000 BP. At 6000 BP Tsuga heterophylla (south) and Picea sitchensis (north) dominated the coast and islands and Quercus garryana and Pseudotsuga on southeast Vancouver Island, but Thuja plicata was infrequent. Southern Interior Plateau vegetation at 6000 BP was more open than today at middle to lower elevations, whereas forests covered the Northern Interior Plateau. Picea forests occurred in northern B.C. Holocene climate phases were: 1) warm dry "xerothermic" ca. 9500-7000 BP, 2) warm moist "mesothermic" ca. 7000-4500 BP, 3) moderate and moist 4500-0 BP, with increasing moisture 8500-6000 BP and cooling (?increased moisture) 4500-3000 BP. B.Cs Hypsithermal had dry and wet stages; 6000 BP occurred in the warm and wet mesothermic stage.